General election in St. Kitts and Nevis, 3 July 1995 : the report... (Commonwealth Secretariat LondonGB, 1996)
Looks at the political background. Examines aspects such as the electoral framework and preparations for the election; the campaign and the news media; and, the poll and the count. Provides a summary of conclusions.
DC